Biocompatibility and osteoconductivity of injectable bone xenograft, hydroxyapatite and hydroxyapatite-chitosan on osteoblast culture - Bachtiar EW; Bachtiar BM; Abas B; Harsas NA; Sadaqah NF; Aprilia R (Dental Journal (Majalah Kedokteran Gigi), 2010)
Background: Bone graft in the form of injectable paste gives several advantages over the powder form as it could be placed in the defect area that has limited accessibility. Purpose: The purpose of this study was to assess biocompatibility and osteoconductivity of an injectable bone xenograft (IBX), injectable hydroxyapatite (IHA) and injectable hydroxyapatite-chitosan (IHA-C) on osteoblastic cell line (MG-63). Methods: Three concentrations (0.25%, 0.5% and 1.0%) of IBX, IHA and IHA-C were supplemented with DMEM culture medium. The viability cells were measured by MTT assay 4 hour after incubation. ALP activity was measured at day 1, 3, 5 and 7. Calcium deposition was tested at day 3 and day 7 by means of Von Kossa staining. Results: MTT assay showed that the viability cells of all the test groups were above 100% compared to the control group. The cell viability of the 0.25% IHA paste was significantly higher (115.02% ± 4.37%, p < 0.05) compared with IBX paste and IHA-C in all concentrations tested. The highest level of ALP secretion of all test groups was found on the fifth day of exposure. The highest level of ALP in the IBX paste group was 0.25% concentration while the highest level of ALP in the IHA-C and IHA paste group was 1% and 0.25%, respectively. In addition, the highest calcium deposition was shown on IHA 1% at day 7 (p > 0.05). Conclusion: It was suggested that adequate biocompatibility and osteoconductivity was evident for all injectable pastes tested.Latar belakang: Bahan tandur tulang dalam bentuk pasta injeksi memiliki kelebihan dibandingkan bila bahan tersebut berupa bubuk, karena lebih mudah diaplikasikan pada daerah yang sulit dijangkau. Tujuan: Penelitian ini bertujuan untuk mengamati sifat biokompatibilitas dan osteokonduktifitas biomaterial tandur tulang dalam bentuk injectable bone xenograft (IBX), injectable hydroxyapatite (IHA) dan injectable hydroxyapatite-chitosan (IHA-C) pada galur sel osteoblas (MG-63). Metode: Bahan tandur tulang IBX, IHA and IHA-C masing-masing dengan konsentrasi 0,25%, 0,5% dan 1,0% dipaparkan dalam larutan medium kultur sel DMEM yang telah disebari sel MG 63. Selanjutnya setelah 4 jam inkubasi maka viabilitas sel diukur dengan cara uji MTT, sedangkan aktifitas fosfatase alkali (ALP) diukur pada hari ke-1 (24 jam), hari ke-3, 5 dan 7. Deposisi kalsium diukur pada hari ke-3 dan ke-7 dengan metoda pewarnaan Von Kossa. Hasil: Uji MTT menunjukkan bahwa pemberian semua jenis bahan pasta injeksi tandur tulang meningkat di atas 100% dibandingkan kontrol. Viabilitas sel pada pemberian 0,25% pasta IHA tampak paling tinggi dibandingkan pasta IBX dan IHA-C pada semua konsentrasi yang diuji. Sekresi ALP tertinggi pada semua kelompok eksperimen terjadi pada hari ke lima setelah paparan bahan injeksi tandur tulang. Sekresi ALP tertinggi pada tiap jenis pasta terjadi pada pemberian IBX 0,25%, IHA-C 1% dan IHA 0.25%. Sedangkan deposisi kalsium tertinggi terjadi pada pemberian 1% IHA setelah 7 hari kultur sel. Kesimpulan: Semua bahan injeksi tandur tulang yang diuji pada kultur osteoblas bersifat biokompatibel dan berpotensi osteokonduktif